Health-related quality of life of patients submitted to correction of heart valve diseases - Maier, Suellen Rodrigues de Oliveira (2023)
Introduction: The measurement of the health-related quality of life construct can reveal the positive repercussions on the lives of patients undergoing corrective valve procedures, as well as revealing points that prevent new surgical approaches. Objective: To identify the health-related quality of life of valvular heart disease in the perioperative period of conventional valve surgery. Methods: This is an integrative literature review. Searches were performed independently in four databases using controlled and uncontrolled descriptors. Eligibility criteria were: original articles that addressed the assessment of the health-related quality of life of valvular patients undergoing valve repair and/or valve prosthesis implantation; in Portuguese, English, and Spanish; with a time frame for convenience between 2015 and 2019. Results: 14 studies comprised the final review sample, despite being studies conducted in different countries and with different designs, it was possible to verify the improvement in health-related quality of life when evaluated through generic instruments in valvular patients after valve surgery. However, in studies in which the assessment of the construct occurred through specific instruments, the existence of factors that can interfere with the quality of life of patients undergoing valve implantation was revealed. Conclusion: It was noticed that there was generally an improvement in health-related quality of life after the surgical intervention.